Analysis of the Application of Positive Psychology Based on Tri Hita Karana in Character Education for Inclusive Students: A Literature Review - I Dewa Ayu Eka Purba Dharma Tari; Ni Ketut Erawati; I Made Sutajaya; I Wayan Suja; Ida Bagus Made Astawa (MultiTech Publisher, 2024)
The aim of this study is to evaluate the role of positive psychology, grounded in the concept of Tri Hita Karana (THK), in developing character education for inclusive students. Research that combines positive psychology with the Tri Hita Karana concept is still scarce, making this study significant in contributing to knowledge on both concepts. In conducting this literature review, a substantial number of documents were examined, including prominent Sinta articles, books, and other relevant materials. The findings reveal that:(1)Positive psychology based on the Parahyangan concept can help students become more religious and grateful; (2)Positive psychology rooted in the Pawongan concept can encourage students to be more tolerant, appreciate one another, care for their surroundings, and communicate effectively; (3) Positive psychology aligned with the Palemahan concept can foster greater environmental awareness among students.In conclusion, the Tri Hita Karana concept and the application of positive psychology are crucial for the character development of inclusive students.